Evaluation of the Effects of Different Mouthrinses on the Color Stability of One Type of Glass Ionomer, Compomer and Giomer - Shaghayegh Razavi; Gazaleh AhmadiZenouz; Hemmat Gholinia; Mohammad Jafari (Mashhad University of Medical Sciences, 2015)
Objectives: The aim of this study was to evaluate the effect of four commercially available mouthrinses on the color stability of one type of glass ionomer, giomer and compomer. Method: 60 disc-shaped specimens, 180 in total (7*2mm), fabricated from each of the following materials: A resin modified glass ionomer Fuji II LC (GC International Corp), a giomer Beautifil II (SHOFU INC) and a compomer Ionosit (DMG). All specimens were stored in artificial saliva at 37˚C for 24 hours in an incubator. The initial colour value (L*,a*,b*) were recorded with spectrophotometer according to CIELAB scale. After baseline evaluation, the specimens were divided into five subgroups, according to the testing and control storage solutions (n=12). Randomly selected specimens from each material were immersed in 20 ml of the treatment solutions (Oral-B Pro Expert, Listerine, Colgate Plax, Irasha) at 37˚c for 24 hours. Each specimen was then subjected to second color measurement. The collected data was statistically analyzed using two-way analysis of variance (ANOVA) and Tukey's HSD at a significance level of 0.05. Results: All samples displayed color changes after immersion in the mouthrinses. The observed color difference showed that mouthrinses have a significant effect on the color shift of tested materials. A significant interaction was found between the materials and the mouthrinses. Overall, discoloration with all mouthrinses was significant when compared to the control specimens stored in artificial saliva. Oral-B induced the highest level of discoloration (ΔE*= 11.62 in Compomer) and the least discoloration was found with Irsha (ΔE*= 1.47 in RMGI). Conclusions: All tested restorative materials showed a color shift after immersion in mouthrinses, amongst which compomer displayed the highest change. Discolorations were clinically perceptible in most of the cases. Thus it can be concluded that daily use of mouthrinses increases the stainability of tested materials.